(untitled) (Ames, Iowa, 2006)
With the shifting of responsibility for designing, planning and managing federally funded programs to state and local government, there is a need for a new group of public servants and others to be aware of how to deal with these responsibilities and challenges. The editors have been active in conducting training with state and local policy makers on how to deal with models using the material in this proposed work. The proposed work outlines and documents a set of community level analytical tools and procedures to assist local decision-making processes. The major goals of the work are to provide a reference for future community policy modeling and analysis efforts, and to provide a group of examples of applications of modeling.
Keywords: Policy sciences,Community development,Chính sách khoa học,Phát triển cộng đồng; United States,Hoa Kỳ